An Innovative Near-Field Communication Security Based on the Chaos Generated by Memristive Circuits Adopted as Symmetrical Key - Kuka, Colin Sokol; Hu, Yihua; Xu, Quan; Alkahtani, Mohammed (IEEE access, 2020)
The new technology solutions are playing an important role in the hardware security. One of the latest techniques is the use of the Memristor as an encryption element. In this paper, it has been introduced a two-column array inductor for Memristor-Based Wireless Power Transfer (M-WPT) systems. The traditional WPT circuits are based on switches, which do require a control circuit for timing and have low data encryption factor. By adopting the memristive Chua's circuit with the chaotic behaviour characteristic, it is possible to create a symmetrical dual-key cryptography. Furthermore, in this innovative solution, the high inductance value of the traditional Chua circuit can be further reduced by using the dynamic effects of the coils flux linkage. The simulation results exhibit the dual-scroll attractors phase portrait, which is available for encryption features. Therefore, the data collected from the phase portrait are used as true random number generator in Python code. Instead of using algorithms, the code can create a symmetrical key for an unique chaotic cryptography. In order to build a prototype, it has been created a PCB design for the whole system. The experiment highlights the unpredictable voltage and current and validates the chaotic behaviour of the transmitter and receiver.